Hadith Musicalization as A New Trend in the Context of At-Tahammul wa al-Adā' - fatimah, fitri; Friyadi, Arif; Zaky, Ahmad (Tebuireng: Journal of Islamic Studies and Society, 2025)
This research discusses hadith musicalization as an innovation in delivering religious messages that combines elements of music and hadith text. Hadith musicalization aims to facilitate understanding, increase retention, and attract the interest of the public, especially the younger generation, through various musical genres and digital platforms in understanding the moral and ethical messages contained in a hadith. As for the context of hadith science, the emphasis of musicalization is given to the importance of maintaining the authenticity and validity of the hadith, as well as paying attention to the sanad, matan, and scientific aspects related to at-Tahammul wal Adā'. Although there is debate regarding the ruling of music in Islam, moderate views from scholars such as Yusuf al-Qardawi support the use of music for positive purposes, as long as it does not contradict the Shari'ah. This research uses descriptive qualitative methods to explore the potential, challenges, and relevance of hadith musicalization in da'wah and education, as well as highlighting the importance of ethics and scholarship in the development of music-based da'wah content. The results of the study are expected to enrich the scientific treasury and provide ethical guidance for da'wah content creators in the digital era.